The Geology of Parliament Buildings 2. The Geology of the Alberta Legislative Building - Burwash, R.; Cruden, D.; Mussieux, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2002)
Summary Alberta's Legislative Building was constructed in Beaux Arts style on the crest of the north bank of the North Saskatchewan River in Edmonton. Excavation for the foundations began in1907; the interior marble and plaster work was completed by 1913. The exterior walls of the basement and first storey were built with grey granodiorite quarried from islands in the mouth of Jervis Inlet, British Columbia. The upper stories consist of Paleocenesand stone from the Bow River valley of southern Alberta. The splendid Corinthian pillars of the main portico required Ohio sandstone to support the Provincial Coat of Arms on the pediment. Marbles from Phillipsburg, Quebec panel the walls of the Rotundaand form the Grand Staircase up to the Legislative Assembly. The Chamber is decorated with spectacular green serpentine marble from Pennsylvania.